Optimization of physicochemical factors for Lignin Peroxidase Enzyme Production utilizing domestic wastewater sludge - Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Jamal, Parveen; Rahman, N A (2005)
A lab-scale study was carried to identify the physicochemical factors of liquid state bioconversion for maximum lignin peroxidase (LiP) enzyme production. The white-rot fungus Phanerocheate chrysosporium collected from the lab stock at IIUM was used LiP production throughout the study. Statistical optimization was carried out to evaluate the physicochemical parameters (factors) through enzyme production by 2-level fractional factorial design with four central points. The polynomial regression model was developed using the experimental data including the effects of linear, quadratic and interaction of the factors. The factors involved were substrate (sludge) and co-substrate (wheat flour) concentrations, temperature, pH, inoculum and agitation. Statistical analysis showed that the optimum conditions were: substrate concentration of 1%, wheat flour concentration of 3%, pH of 4, inoculum of 3% and agitation of 100 rpm. Under these conditions, the model predicted the enzyme production to be 833.9 U/L. Analysis of variance (ANOVA) of the design showed a high coefficient of determination (R2) value of 0.94, thus ensuring a satisfactory adjustment of the quadratic model with the experimental data.